Poscolonial Peruvian Sheep and Their Digital Dreams: Pure Data as a Tool for Conceptual Reconfiguration in Peruvian Musical Education - Gastón, José Ignacio López Ramírez (Revista Vórtex, 2021)
In this work, I discuss the use of Pure Data as the main tool for the development of paradigmatic changes in Peruvian musical education, through the implementation of the Laboratorio de Música Electroacústica y Arte Sonoro of the Universidad Nacional de Música in Lima - Perú. This analysis is made taking under consideration the particularities present in the development of the study of technology-based music in the country and the historical shortcoming that have marked that development. This work complements my previous research regarding the relevance of specific social narratives present through the history of the nation in regards to technology and musical innovation. In that sense, it presents a historical that seeks to revert the course of a musical learning history that excludes technology based musical practices associated with Pure Data, from becoming part of the official processes for musical creation in the country.